Release of iron from transferrin by phosphonocarboxylate and diphosphonate chelating agents - Harris, Wesley R.; Brook, Claire E.; Spilling, Christopher D.; Elleppan, Sampathkumar; Peng, Wang; Xin, Meiguo; Wyk, Jennifer Van (Journal of inorganic biochemistry, 2004)
The rates at which phosphonocarboxylate and diphosphonate ligands remove iron from the serum iron transport protein transferrin at 25 °C and pH 7.4 have been evaluated. These ligands show a combination of saturation and first-order kinetics with respect to the free ligand concentrations. The ability of the ligands to remove iron from transferrin appears to be subject to steric restrictions that are essentially identical to those associated with the ability of a ligand to substitute for the synergistic carbonate anion. This observation supports the hypothesis that the first-order component for iron removal involves a mechanism in which the rate-limiting step is the slow substitution of the synergistic carbonate by the incoming chelating agent. Studies on monoferric transferrins indicate that phosphonocarboxylates are unusually effective at removing iron from the C-terminal site of the protein. Difference UV spectroscopy has been used to show that the phosphonocarboxylates bind strongly to apotransferrin. It is suggested that the rapid release of iron from the C-terminal site may be due to the binding of the ligand to an allosteric anion-binding site in the C-terminal lobe of the protein.